Florescimento e viabilidade do pólen de Astrocaryum acaule Mart. na Amazônia Ocidental - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
The Arecaceae family has great diversity and socioeconomic importance with species known to be suppliers of products for various purposes, such as Astrocaryum acaule Mart, an Amazonian palm tree that produces fruits consumed by the traditional populations of the region. The characterization of the specie in terms of floral biology and pollen viability generates knowledge that can contribute to the conservation and genetic improvement of the species. The objectives of this work were to study flowering, pollen viability and define an efficient method for collecting and storing pollen. Phenological events were monitored in 30 genotypes over a 12-month period. The characterization of the floral biology of the species was carried out with monitoring of floral events. For the study of pollen viability pollen was collected in inflorescences of five individuals of the species. Three dye solutions were tested to determine pollen viability: Tetrazolium (0.1%), Cotton Blue (0.05%) and Triphan Blue (0.2%) with pollen evaluation for 360 days. The ideal culture medium for pollen germination was determined and germination was evaluated during the same period. The analyzes of phenology and floral biology were expressed using descriptive statistics, and the pollen viability data submitted to analysis of variance and subjected to the Tukey test when there was a significant difference, with the help of the Statistica Software. The annual flowering cycles occur from June to August and November to January. There was a record of fruiting in all months, except in July and August. The anthesis chronology occurs in the period of three consecutive days with the female phase, interval between phases and the male phase. The species shows thermogenesis with a variation of 3 ° C in the temperature in the inflorescence compared to the ambient temperature. The viability of fresh pollen was considered high, being greater than 80% in all treatments. The highest percentage of germination of fresh pollen occurred in the culture medium with 100 g L⁻¹ of sucrose and addition of Ca (NO₃) ₂2H₂O (60.08%). At the end of the evaluation period (360 days), pollen grains stored at lower temperatures (-20 ° C and -80 ° C) showed greater viability, with an average higher than 60% by the Tetrazolium test and 20% germination in sucrose and dehydrated calcium. A. acaule has two defined annual flowering and fruiting cycles, the periods from June to August and November to January being the best for collecting pollen and performing crosses. The Tetrazolium dye and the calcium agar medium are the most efficient for analyzing pollen viability and germination. Pollen stored for 360 days maintains greater viability when stored at low temperatures.
Flowering and viability of pollen from Astrocaryum acaule Mart. in the Western Amazon
Floración y viabilidad del polen de Astrocaryum acaule Mart. en la Amazonía occidental
Keywords: Palmeira amazônica; Hibridação interespecífica; Hibridação vegetal; Polinização por insetos; Corante Tetrazólio; CIÊNCIAS AGRÁRIAS; Hibridação; Polinização controlada; Armazenamento de pólen; Tucumã-í; Biologia floral